Servicio al cliente como indicador de calidad en la compañía de transporte escolar e institucional Riveras Del Babahoyo S.A. cteirb (ecuador) - Vega Fernández, Hugo Alberto (2023)
The realization of this case study is based on customer service as a quality indicator of the School and Institutional Transportation Company Riveras Del Babahoyo S.A., quality indicators allow evaluating the performance of products, services and people, through this study aims to determine how it affects the way in which the service is provided to transport users to determine if the service provided is of quality and the client has the desired satisfaction. The service provided to the client is relevant in the Compañía de Transporte Escolar e Institucional Riveras Del Babahoyo S.A., therefore, analyzing the administrative management processes will also contribute to detecting those indicators so that the service remains within the quality standards in the transportation of school and institutional personnel. Measuring customer satisfaction and that it is high compared to other ground transportation service providers is an indicator that within the company the efforts of the administrators give positive results to keep a satisfied customer and that they continue contracting the services offered by the Company. of School and Institutional Transportation Riveras Del Babahoyo S.A.